2022
DOI: 10.1002/lio2.752
|View full text |Cite
|
Sign up to set email alerts
|

Extensive hearing loss induced by low‐frequency noise exposure

Abstract: Background With little attention given to low‐frequency traffic noise and our understanding that cochlear function may be highly susceptible to low‐frequency noise, there is an urgent need to determine traffic noise‐induced hearing loss (NIHL), not only the hearing loss at low frequency but also the possible high‐frequency hearing loss. Methods The current study aims to investigate the potential for extensive hearing loss induced by exposure to 0.063 kHz octave band noise (OBN), which is an important component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…This leads to NIHL that tends to be greatest at low frequencies ( McCombe et al, 1995 ). Several studies involving animals have shown that exposure to intense low-frequency tones or bands of noise can lead to temporary or permanent hearing loss and damage to the hair cells in the cochlea over a wide range of frequencies ( Burdick et al, 1978 ; Harding & Bohne, 2009 ; Liu et al, 2022 ; Mills et al, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to NIHL that tends to be greatest at low frequencies ( McCombe et al, 1995 ). Several studies involving animals have shown that exposure to intense low-frequency tones or bands of noise can lead to temporary or permanent hearing loss and damage to the hair cells in the cochlea over a wide range of frequencies ( Burdick et al, 1978 ; Harding & Bohne, 2009 ; Liu et al, 2022 ; Mills et al, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…The noise produced by passing vehicles poses a significant source of disturbance and annoyance for residents, leading to potential negative impacts on their quality of life and health. Several research reports have linked long-term exposure to traffic noise with various health issues, including hearing loss [7,8], cardiovascular disease [9,10], sleep disturbances [11][12][13], and impaired cognitive function [14]. Moreover, traffic noise can result in annoyance [15], stress [16], and tinnitus [17].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Cai et al proposed four types of anisotropic PMs, which are constructed by changing the thin-end points along the space-diagonal, and further explored the effects of anisotropy on the acoustic properties and figure of merit [25]. A novel double-cone PM with hexagonal unit cell arrangements was examined by Li et al, to understand the effects of structural parameters on acoustic properties [26]. The influences of crosssection shapes of PMs (i.e., regular triangles, squares, hexagons, and others) on acoustic properties were investigated numerically, and the relationship between acoustic properties and cross-section shapes was revealed [27].…”
Section: Introductionmentioning
confidence: 99%